2015
DOI: 10.1161/circimaging.115.003651
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Left Ventricular Remodeling Among Competitive Athletes

Abstract: E xercise-induced cardiac remodeling (EICR) refers to changes in cardiac structure and function that occur in response to exercise training. Numerous structural aspects of EICR (ie, athlete's heart) including ventricular chamber enlargement 1 and hypertrophy 2 have been described, and several key determinants of the EICR process including age, 3 sex, 4 ethnicity, 5 and sporting discipline 6,7 have been established. However, contemporary understanding of EICR is based largely on cross-sectional data derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 32 publications
6
73
2
4
Order By: Relevance
“…2CH: apical two chamber view; 4CH: apical four chamber view; APLAX: apical parasternal long axis view; E: early diastolic filling (E-wave); A: late diastolic filling (A-wave); E (cm/s): early diastolic velocity of mitral annulus; A (cm/s): late diastolic velocity of mitral annulus; S (l/s): systolic strain rate; E (l/s): early diastolic strain rate; A (l/s): late diastolic strain rate. Weiner et al, 2015) demonstrated that the magnitude of exercise-induced cardiac remodelling differs substantially across athletes. Genetic, epigenetic and environmental factors may contribute to the inter-individual differences of remodelling (Eijsvogels & Thompson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2CH: apical two chamber view; 4CH: apical four chamber view; APLAX: apical parasternal long axis view; E: early diastolic filling (E-wave); A: late diastolic filling (A-wave); E (cm/s): early diastolic velocity of mitral annulus; A (cm/s): late diastolic velocity of mitral annulus; S (l/s): systolic strain rate; E (l/s): early diastolic strain rate; A (l/s): late diastolic strain rate. Weiner et al, 2015) demonstrated that the magnitude of exercise-induced cardiac remodelling differs substantially across athletes. Genetic, epigenetic and environmental factors may contribute to the inter-individual differences of remodelling (Eijsvogels & Thompson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At study enrollment, these subjects exercised for ≤30 minutes, 3 times per week, and through a supervised, incremental exercise training program achieved a peak exercise regimen of 7 to 9 hours per week at the end of 1 year, in preparation for a marathon race. Therefore, it is noteworthy that these subjects were, on average, over 10 years older than the subjects of Weiner et al 9 and reached an exercise dose at the end of the study that reflected the baseline exercise dose of the subjects in the current cohort.…”
Section: See Article By Weiner Et Almentioning
confidence: 75%
“…Although also reporting a phasic response to EICR, in contrast to Weiner et al, 9 Arbab-Zadeh et al 11 observed that in their population, the initial increase in left ventricular mass resulted from increased left ventricular wall thickness in a pattern of concentric hypertrophy in the first 6 to 9 months, with subsequent left ventricular dilatation at 9 to 12 months, producing the final picture of eccentric hypertrophy.…”
Section: See Article By Weiner Et Almentioning
confidence: 81%
See 1 more Smart Citation
“…High volumes of exercise training improve cardiovascular risk factors [42], and cause an initial increase in left ventricular chamber size followed by an increase in wall thickness during chronic exercise training [43].…”
Section: Too Much Exercise?mentioning
confidence: 99%